Time to re-set our thinking about airways disease: lessons from history, the resurgence of chronic bronchitis / PBB and modern concepts in microbiology - Everard, Mark L.; Priftis, Kostas; Koumbourlis, Anastassios C.; Shields, Michael D. (Frontiers in Pediatrics, 2024)
In contrast to significant falls in deaths due to lung cancer and cardiac disease in westernised countries, the mortality due to 'chronic obstructive pulmonary disease' (COPD) has changed little in recent decades while 'the incidence of bronchiectasis' is on the rise. The current obsession with producing guideline for these two 'diseases' of the airways has been a major factor in this lack of progress in both treatment and prevention. The elephant in the room is that neither is a disease but rather they are the consequence of progressive untreated airways inflammation.To make this case it is important to review the evolution of our understanding of airways disease and how a pathological appearance (bronchiectasis) and an arbitrary physiological marker of impaired airways (COPD) became 'diseases'.Insights into the natural history of airways disease can best be obtained from the pre-antibiotic era. The dramatic impacts of antibiotics on the prevalence of significant airways disease, especially in childhood and early adult life, have largely been forgotten and will be revisited as will the misinterpretation of trials undertaken in those with chronic (bacterial) bronchitis.Over the past couple of decades paediatricians have noted the progressive increase of what has been termed persistent bacterial bronchitis (PBB) which has all the same characteristics of the 'chronic bronchitis' so common in young children in the preantibiotic era while the radiological appearance of bronchiectasis is again becoming more common in children and, latterly, adults. Adult physicians continue to question the reality of PBB but in one study attempting to assess the role of antibiotics in adults with consistent symptoms the investigators found the majority of patients who would qualify were already on long term macrolides! Over recent decades we have come to appreciate the importance of the respiratory microbiome and have recognised the ability of bacteria to persist in potentially hostile environments using strategies such as biofilms, intracellular communities and persister bacteria. This is a challenging field that is likely to require new approaches to diagnosis and treatment, but it needs to be embraced if real progress is to be made.